Modeling and analysis of optimal performance of a coal-fired power plant based on exergy evaluation - Khaleel O.J.; Ibrahim T.K.; Ismail F.B.; Al-Sammarraie A.T.; Hassan S.H.B.A. (Elsevier Ltd, 2023)
Coal fired power plant; Coal fueled furnaces; Exergy; Fossil fuel power plants; Steam power plants; Coal-fired; Condition; Design condition; Feedwater; Feedwater heater; Fossil fuel consumption; Modelling and analysis; Optimal performance; Optimisations; Steam extraction; Coal